Dairy husbandry information needs of farmers in different agro-climatic zones of Uttar Pradesh - SINGH, PUSPENDRA KUMAR; TIWARI, RUPASI; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2018)
The present study was undertaken to examine the information needs of farmers using mKisan services with respect to different dairy husbandry practices. Results of weighted mean score revealed that farmers have higher information need about feeding and watering practices (2.20) followed by marketing of farm produce (2.19), breeding practices (2.18), health care practices (2.12), management practices (2.11) and fodder production and grass land management (2.10) with their information deficiency level of 73.3, 73.0, 72.7, 70.7, 70.3 and 69.9%, respectively. Major needs were related to recommended feeding practices of dairy cattle (2.38) and area specific mineral mixture (2.30). Information about procurement agencies in area (2.15) and day-to-day price variation of different farm produce (2.11) were also found of great concern in marketing of farm produce. Farmers have higher information need about estrus detection and time of insemination (2.30), selection of dairy cattle (2.21) and heifer management (2.18) in the domain of breeding. In health care practices, information about preventive measure against diseases (2.23) and vaccination schedule (2.17) was much needed. In management practices, information need for calf management (2.20) and clean milk production (2.19) was found to be highest. In fodder production and grass land management domain, information need about locally suitable fodder varieties (2.16) and management for fodder availability round the year (2.14) were at highest priority. Information need over different aspect of dairy husbandrypractices had significant variation across the different agro-climatic zones of Uttar Pradesh. North Eastern Zone and Bundelkhand Zone were found the highest information deficient zones in Uttar Pradesh.